Distribution of dipole oscillator strengths for the formation of excited hydrogen atom from C2H2. Issue 14 (January 2020) - Kumagai, Y; Odagirit, T; Nakano, M; Suzuki, I H; Hosaka, K; Kitajima, M; Kouchi, N
Synopsis: Dipole oscillator strengths for the formation of excited hydrogen atom from C2 H2 were measured to investigate formation and decay of molecular superexcited states. It seems that non-adiabatic transition plays an important role in the formations of the hot hydrogen atom.